2013
DOI: 10.1073/pnas.1215506110
|View full text |Cite
|
Sign up to set email alerts
|

Predicting climate effects on Pacific sardine

Abstract: For many marine species and habitats, climate change and overfishing present a double threat. To manage marine resources effectively, it is necessary to adapt management to changes in the physical environment. Simple relationships between environmental conditions and fish abundance have long been used in both fisheries and fishery management. In many cases, however, physical, biological, and human variables feed back on each other. For these systems, associations between variables can change as the system evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
201
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(207 citation statements)
references
References 32 publications
1
201
1
3
Order By: Relevance
“…In fact, it has been suggested that to effectively manage aquatic resources that management needs to adapt to changes in the physical environment [35]. The ability to adapt to changing conditions is greatly constrained when long-term average conditions are solely evaluated.…”
Section: Comparison With Previous Researchmentioning
confidence: 99%
“…In fact, it has been suggested that to effectively manage aquatic resources that management needs to adapt to changes in the physical environment [35]. The ability to adapt to changing conditions is greatly constrained when long-term average conditions are solely evaluated.…”
Section: Comparison With Previous Researchmentioning
confidence: 99%
“…Implicitly, the stock-recruit relationship does not account for climate variability and change, although environmental terms can be added to expand this type of model. Equation-free models reconstruct the behavior of systems directly from time-series data without the standard assumption of equations for the relationships between variables and have been applied to the Pacific sardine (Deyle et al 2013). However, such models are unable to project the future state of ecosystems on the scale of climate change.…”
Section: Modelsmentioning
confidence: 99%
“…Judgments regarding management performance should be made in the context of the system that produced those decisions. Relevant system features include whether the management process is based on best 10 Since 2012, sardine abundance, which is affected by ocean conditions as well as fi shing mortality (Deyle et al, 2013;CDFW, 2015), has declined precipitously in Oregon and Washington as well as California. California sardine landings are now lower than they have been since 1990, and northern anchovy is now the largest (albeit still modest) component of CPS fi nfi sh catch (PFMC, 2014b).…”
Section: Discussionmentioning
confidence: 99%